Increasing the operating time of hollow fiber membrane bundles used for water ultrafiltration - Ciocănea Adrian; Simionescu Ștefan-Mugur; Opriș Florin (E3S Web of Conferences)
In order to increase the interval between cleanings of a hollow fiber membrane bundle (HFMB) used for water ultrafiltration, a numerical study and an experimental test were conducted. The relation between the water flow rate and shear stress along the hollow fiber membrane wires (HFMW) was studied for three geometries. Three angles (α = 900,450,00) for the intake flow pipe (di = 25 mm) against the horizontal axis of a cylinder (Dc = 100 mm; L = 600 mm) containing one hollow fiber membrane wire (dw = 1 mm) were chosen for the numerical investigation; five different water flow rates (Q = 8…16 l/min) were considered. The values for the shear stresses along one membrane wire placed along the cylinder's central axis were computed. The findings show that the best geome1try for enhanced shear stress is obtained for α = 00. For this geometry a mean value of 1.1 Pa for the shear stress was obtain along the first 1/3 of the membrane wire at a minimum flow rate of Q = 8 l/min. Higher values for water flow rates do raise shear stress but increased energy consumption is needed. The tests were carried out on a HFMB with molecular weight cut-off (MWCO) of 0.097 μm, that was put in a glass cylinder with a horizontal axis, for μ = 900, μ = 00, and Q = 8 l/min. The results confirmed the conclusions of the numerical study i.e. the filtering capacity of the membrane was maintained higher by 6-6.5% for α = 00 comparing to α = 900 due to shear stress increase. For the flow rate of Q = 12 l/min the filtering capacity of the membrane did not increased. The study confirmed the hypothesis that for certain geometries there could be settle down optimum flow rates to minimize energy consumption during membrane operation but comprehensive research is needed.